Re-Thinking Pan-Africanism and African Integration - Keith Gottschalk (African Journal of Political Science)
It is 129 years since an African-American journalist in Chicago coined the word “Pan-Africanism”. Pan-Africanism began as a gift of the diaspora to the African continent. These civil society initiatives in the diaspora culminated in an elaborate permanent, continental, state-centric institutionalisation, starting six decades ago with the Organisation of African Unity (OAU) in 1963. Its current dispensation is the African Union, and sub-regional organisations such as the Economic Community of West African States, the East African Community, and the Southern African Development Community. Diplomacy, peace-making, and economic integration have been prominent dimensions of Pan-African endeavours. As well as the continuing growth of African diasporas in countries ranging from the USA to China, we need to note the precarious position of growing intra-African diasporas in other African countries. Pan-Africanism will remain fragile until it can grow mass support, as opposed to being usually limited to intellectuals and some members of the ruling elites. African integration has not yet achieved the extraordinary supra-national aspirations enunciated in its treaties. Taken literally, they would require such significant concessions of national sovereignty as to amount to a post-Westphalian dispensation. But dense, overlapping networks of inter-governmental organisations, and continental NGOs, continue to proliferate and have substantial successes to date. These range from multi-lateral peace-enforcement expeditionary forces, to free trade areas and the start of common markets. Diplomatic alliances mark the essence of most sub-regional organisations and explain why they continue to thrive, notwithstanding the “spaghetti bowl” incomprehension of some economists and law scholars about their entanglement. We can confidently predict the continued growth of inter-governmental organising, sub-regional and continental NGOs, and Pan-African corporate expansion of an order of magnitude above what currently exists.